Presenting an Operational Model for Sustainability Evaluation of Higher Education Institutions: University of Tehran as a Case of Study - Emad Malekinia; Abbas Bazargan; Sedighe Feizi (Allameh Tabataba'i University Press, 2016)
The main goals of sustainability evaluation is measuring the educational, research, outreach and other university programmes based on sustainable development's principles and concepts. The main purpose of this study is indentification of sustainability factors and criterias, and then evaluation of Tehran University sustainability based on them. Exploratory mixed method research used to accomplish this goal. In the qualitative part, the focus groups research method and individual interview was used and in the quantitative part analytical-descriptive research method was employed at the University of Tehran area. In the qualitative part, purposive non-probability sampling method and in the quantitative part, stratified sampling method was used for selection of students and faculty. The results of the study show that the main factors of sustainability evaluation include: education, research, governance system, environmental management system, sustainable financing system, and outreach. These factors can be assessed using 34 criteria and 81 indicators. The results of the sustainability assessment at UT show that significant difference between present situations with ideal level. Also, Analysis of data using inferential statistics indicates that there is a significant difference between the views of faculty members and students regarding the sustainability condition of UT. Identified model in this research is a pioneer initiative in sustainability evaluation of Iran's higher education institutions. This model can be used by senior managers of higher education system and university leaders.